PENGARUH KONSEP DIRI, SIKAP SISWA PADA MATEMATIKA, DAN KECEMASAN SISWA TERHADAP HASIL BELAJAR MATEMATIKA - Leonard & Supardi US (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Effects of Students Self-Concept, Behavior towards Mathematics, andAnxiety on Mathematics Learning Achievement. This study aims to investigateeffects of students self-concept, behavior towards mathematics, and anxiety on themathematics learning achievement using the Path Analysis. The results show that:(1) there is a positive direct effect of positive self-concept on students mathematicsachievement; 2) there is no indirect effect of self-concept on students mathematicsachievement through anxiety; 3) there is no indirect effect of students behaviortowards mathematics on students mathematics achievement through anxiety; 4)there is a negative direct effect of anxiety on students mathematics achievement;and 5) there is a positive direct effect of self-concept on students behavior towardsmathematics.Keywords : self-concept, students behavior towards mathematics, anxiety, learning achievement, path analysis